Pelaksanaan Kegiatan Apresiasi Seni Oleh Pendidik AUDNon Gelar PAUD Di Desa Cipicung Kecamatan Banyuresmi - Shelly Pratiwi; Hilmi Imamatus Sadiah (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2026)
This study is motivated by field findings showing that in several PAUD/RA institutions in Cipicung Village there are educators who do not hold formal degrees in early childhood education or the arts. Based on initial observations and interviews, this condition has led to limited teacher understanding in carrying out art appreciation activities according to proper stages. As a result, teachers tend to focus only on art-making activities without including appreciation. The purpose of this study is to identify the extent of educators’ understanding of the concept of art appreciation and the obstacles to its implementation. This research employed a descriptive qualitative approach using observation, interview, and documentation techniques. Interviews revealed three non-degree early childhood teachers at RA Suandika, TK Al-Ajra, and PAUD Al-Ajra. The observations indicated that art appreciation practices were not optimal. TK Al-Azra practiced appreciation by giving verbal praise but did not display children’s works. RA Suandika displayed children’s works but did not provide verbal praise. Meanwhile, PAUD Al-Azra had not implemented appreciation at all. Factors contributing to the lack of optimal implementation include limited facilities, time, and teacher understanding. To improve these practices, teachers are encouraged to provide simple forms of appreciation, manage time specifically for appreciation, and participate in training to enhance their understanding of art appreciation. Such activities are crucial for fostering children’s self-confidence.Keywords: Art Appreciation, Non-Degree Teachers, PAUD